Osmotic dehydration effects on mass transfer kinetics and characteristics of fried banana (Musa balbisiana) chips - Polo Ruiz, Gustavo (2020)
ABSTRACT This study evaluated the osmotic dehydration (OD) treatments (using sucrose at 60 °Brix and a solution of salt 1.5% (m/m) with sucrose at 45 °Brix) in banana slices. The effects on the mass transfer kinetics (water loss and solids gain) were evaluated and described using the Page, Weibull, Peleg, Azuara, and Lewis mathematical models. Besides, the effect of OD on fat content, instrumental colour, and sensorial attributes was assessed after the frying process. The results showed that water loss occurs firstly and more quickly than solids gain. At the end of OD, the highest water loses (0.31 g water/g sample) and solids gain (0.42 g solid/g sample) were reached using sucrose OD treatment. The water loss and solid gain behaviour were described not only by the kinetics parameters but also by equilibrium parameters values of mathematical models. Furthermore, after frying, the Control samples presented a fat content of 15.5 ± 0.3%, where the moisture reduction during OD allowed to obtain fried samples with lower fat content (9.8 ± 0.3%), as well as, their instrumental colour was significantly affected mainly decreasing the lightness. Regarding sensorial attributes of fried chips, it was preferred the colour and flavour of samples with sucrose OD treatment, however, the Control samples obtained the best scores in texture attribute. Therefore, it was demonstrated that mass transfer of water and solid during osmotic dehydration treatments did not occur similarly and there were influenced by the concentration and type of osmotic solution. In addition, the modifications in structure and composition during osmotic treatments allowed to obtain a low-fat product with good sensorial attributes. Keywords